PERPUSTAKAAN MILENIAL BANJARBARU - Armila, Armila; Nurfansyah, Nurfansyah (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2021)
Technological advances have now mastered several aspects, namely in the world of education, fashion, lifestyle and the world of architecture. For example libraries, in the past, libraries were seen from the number of books collected and also how big the library building was but for now all that has changed, libraries are now required to be able to follow the wishes of its users. In this case the users are the millennial generation who have characteristics that are close to technology, like convenience and are free-spirited. According to a survey from the Boston Consulting Group and the University of Berkley about the millennial generation, the conventional reading interest of millennials has decreased and they prefer to use smartphones to read and libraries are considered unimportant to them. The design of the Banjarbaru Millennial Library uses the Behavioral Architecture method and the Blurring Architecture concept. This design aims to create a library in accordance with the characteristics of millennials who like freedom by implementing this freedom into its buildings